FACTORS AFFECTING COMPLETE OF BASIC IMMUNIZATION FOR INFANTS IN THE JEULINGKE COMMUNITY HEALTH CENTER WORK AREA BANDA ACEH CITY IN 2020 - Marzuki, Marzuki; Jannah, Mifthahul; Mawardi, Mawardi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2021)
Background: Basic immunization is a mandatory health program implemented by the government for infants aged 0-12 months as an effort to increase immunity to diseases that can be prevented by immunization. The results of the initial data tracing at the Jeulingke Health Center in Banda Aceh City in 2020, showed that 20% of villages had achieved Universal Child Immunization (UCI), and 80% of villages had not achieved UCI. The purpose of this study was to determine the factors that influence the completeness of complete basic immunization in infants in achieving Universal Child Immunization (UCI). Methods: This study is a descriptive analytic with a cross sectional design. Sampling was done by proportional sampling as many as 81 mothers who have babies 9-12 months. Data analysis using Chi Square test. Results: This study showed that infants who were given complete immunization were 45.7% and those who incomplete were 54.3%. The bivariate analysis showed that there was a relationship between maternal knowledge (p-value 0.001), family support (p-value 0.001), the role of health workers (p-value 0.025), and the issue of haram in immunization (p-value 0.046) with the completeness of basic immunization complete in infants. Conclusion: It is hoped that Puskesmas officers can conduct counseling in the community to increase mother's knowledge about the benefits of completing basic immunizations for their babies and mothers should immunize their children on time, considering that immunization is very important to equip their children with health in the future.